EFFORTS OF THE REPUBLIC OF UZBEKISTAN AIMED AT THE STABILIZATION OF MILITARY-POLITICAL SITUATION IN AFGHANISTAN (Neo Science Peer Reviewed Journal, 2023)
The report is devoted to the approaches of the Republic of Uzbekistan to resolving issues related to security and development in Afghanistan. In addition, a retrospective analysis of the efforts of the Republic of Uzbekistan aimed at achieving peace and stability in Afghanistan is carried out.